The relationship between worker health (hemoglobin levels and blood pressure) and work fatigue toward worker performance at PT. Aksar Saputra Lines - Citra Rahmandani Pratiwi; Yusuf Sabilu; Indah Ade Prianti (Indonesian Journal of Health Science, 2026)
Worker health and fatigue levels are important factors in occupational safety and health that influence work performance and productivity, particularly among employees in the shipping industry. This study aimed to examine the relationship between workers' health conditions, as measured by hemoglobin levels and blood pressure, and work fatigue with employee performance at PT. Aksar Saputra Lines in 2026. This research employed an analytical observational design with a cross-sectional approach. A total of 50 respondents were included in the study using a total sampling technique. Data were collected using a standardized questionnaire that had passed validity and reliability testing, supported by direct measurements of respondents' hemoglobin levels and blood pressure. The independent variables in this study were hemoglobin levels, blood pressure, and work fatigue, while the dependent variable was employee performance. Data were analyzed using univariate and bivariate analyses with the chi-square test at a significance level of 5%. The findings revealed significant relationships between hemoglobin levels (p = 0.031), blood pressure (p = 0.012), and work fatigue (p = 0.001) and employee performance. Employees with poorer health conditions and higher levels of fatigue tended to demonstrate lower work performance. Based on these findings, it can be concluded that workers' health conditions and fatigue levels are significantly associated with employee performance.